Sorption of Toxic Compounds from Aqueous Solution by Carbon and Carbon Composites - D.I. Shvets (Adsorption Science & Technology)
Investigations regarding the possible use of carbon and carbon composites for environmental decontamination, with particular reference to reservoirs, have demonstrated that the variety of structural forms of carbon materials are the principal cause for their synergism and high selectivity in adsorption processes. The mechanisms of such processes need more detailed study in order to develop practical recommendations for their large-scale application.